2017 25th Mediterranean Conference on Control and Automation (MED) 2017
DOI: 10.1109/med.2017.7984168
|View full text |Cite
|
Sign up to set email alerts
|

Steady state evaluation of distributed secondary frequency control strategies for microgrids in the presence of clock drifts

Abstract: ©2017 IEEE. This is an author produced version of a paper published in Proceedings of 25th Mediterranean Conference on Control and Automation. Personal use of this material is permitted. Permission from IEEE must be obtained for all other users, including reprinting/ republishing this material for advertising or promotional purposes, creating new collective works for resale or redistribution to servers or lists, or reuse of any copyrighted components of this work in other works. Uploaded in accordance with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The analysis focuses on steady-state properties of the frequency control and active power sharing, as well as on stability properties considering clock drifts. It covers the results presented in [27]- [30], and extends them with additional policies, with steadystate expressions of the equilibrium points, with a robust stability characterization of the equilibrium points, and/or with experimental validation. In addition, it complements the analysis of local policies given in [32] because the focus of this paper is mainly on control schemes that exchange control data to accomplish the frequency control.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The analysis focuses on steady-state properties of the frequency control and active power sharing, as well as on stability properties considering clock drifts. It covers the results presented in [27]- [30], and extends them with additional policies, with steadystate expressions of the equilibrium points, with a robust stability characterization of the equilibrium points, and/or with experimental validation. In addition, it complements the analysis of local policies given in [32] because the focus of this paper is mainly on control schemes that exchange control data to accomplish the frequency control.…”
Section: Introductionmentioning
confidence: 81%
“…In [28] it is shown that local clock drifts in local integral controllers designed for frequency regulation make the MG unstable, results that are illustrated with simulations. The work by [30] provides an steady-state analysis of several distributed secondary frequency control strategies with consideration to clock drifts, illustrated with simulation results. In [31], and focusing in angle droop control, stabilizing controllers based in consensus are derived to remove the negative effects that drifts have on frequency control and power sharing.…”
Section: Introductionmentioning
confidence: 99%
“…A GFI is a voltage source inverter which is controlled using pre-defined voltage and frequency values [2], [3]. Inspired by conventional power systems, a hierarchical control strategy is advocated in case of MGs [4], out of which, in this paper, we are interested in distributed secondary frequency control [1], [5]- [9] which uses local information as well as neighboring information over a communication network to ensure frequency restoration and power sharing (PS).…”
Section: Introductionmentioning
confidence: 99%
“…In an inverter-dominated MG, each inverter typically has only a local understanding of time, which leads to clock inaccuracies [10]. In practice, clock drifts [11], [12] are non-negligible phenomena in distributed MG control [1]. A main reason for this is that in the presence of clock drifts, the internal frequency of an inverter differs from its actual electrical frequency [10], [13].…”
Section: Introductionmentioning
confidence: 99%
“…The lower control layers, i.e., primary and secondary control, are designed such that the MG can run autonomously for several minutes, so providing power setpoints to the units on the same timescale is sufficient. These control layers ensure a desired power sharing (see, e.g., [46], [47]) among the grid-forming units.…”
Section: Microgrid Modelmentioning
confidence: 99%